Preparation method of multi-functional-group synergistic modified aluminum silicate nanofiber membrane
Through the multi-step modification method, aluminium silicate nanofibers are synergistically modified to form a nanofiber membrane rich in double bonds and polycarboxyl groups, solving the shortcomings of traditional adsorbent materials in removing heavy metal ions, and achieving efficient adsorption and structural stability improvement.
Patent Information
- Application Number
- CN202510331686.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-20
AI Technical Summary
Traditional adsorbent materials have limited capabilities and high costs in removing heavy metal ions, and aluminum silicate nanofibers as adsorbents have problems such as difficult to recover and single functional groups.
Through the multi-step modification method, the aluminum silicate nanofibers are modified in a synergistic manner by using chemical substances such as aminosilane coupling agent, 1,3-dichloropropanol and itaconic acid to form a nanofiber membrane rich in double bonds and polycarboxyl groups.
It realizes efficient adsorption of heavy metals, solves the problem that nano powder materials are not easy to recover, and improves the structural stability and adsorption performance of the film.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum silicate fiber membranes, and in particular to a method for preparing a multi-functional group synergistically modified aluminum silicate nanofiber membrane. Background Art
[0002] At present, a variety of effective technologies have been developed for the removal of heavy metal ions in wastewater, including flocculation, chemical precipitation, membrane filtration, ion exchange and adsorption. Among them, the adsorption method is widely used due to its advantages such as simple operation and recyclable adsorbent. However, traditional adsorbents have limited capacity and high cost in removing heavy metal ions. As a new type of nano-mineral fiber material, aluminum silicate nanofibers have the advantages of being non-toxic, environmentally friendly, easy to regenerate, and having a highly developed pore structure, huge specific surface area and excellent cation exchange performance. Therefore, they have shown great application potential in the field of heavy metal wastewater treatment. However, aluminum silicate nanofibers exist in the form of powder. Direct use as an adsorbent requires cumbersome secondary separation, and it is difficult to completely separate them. There is a risk of leakage and it is easy to cause secondary pollution to the environment. In addition, the types of its surface functional groups are relatively single and limited in number, which to a certain extent limits its adsorption efficiency for heavy metal ions. Summary of the invention
[0003] In view of the above-mentioned defects of the prior art, the present invention provides a method for preparing a multi-functional group synergistically modified aluminum silicate nanofiber membrane, which achieves efficient adsorption of heavy metals and solves the problem that aluminum silicate nanofibers are difficult to recycle.
[0004] The technical solution of the present invention is as follows: A method for preparing a multi-functional group synergistically modified aluminum silicate nanofiber membrane comprises the following steps: (1) Aluminum silicate nanofibers are modified by using an aminosilane coupling agent to obtain amino-modified aluminum silicate nanofibers; (2) grafting the polyamino compound onto the surface of the amino-modified aluminum silicate nanofibers by a substitution reaction between amino groups and chlorine and utilizing the cross-linking effect of 1,3-dichloropropanol to obtain multifunctional aluminum silicate nanofibers; (3) modifying the surface of the multifunctional aluminum silicate nanofibers with 2-butenal by an ammonia-aldehyde condensation reaction, thereby obtaining multifunctional aluminum silicate nanofibers rich in double bonds; (4) using itaconic acid as a monomer and the double-bond-rich multifunctional aluminum silicate nanofibers as a crosslinking agent, performing crosslinking polymerization, and then performing suction filtration to form a membrane, and obtaining a film having a gram weight of no more than 15 g / m 2 Multi-functional groups synergistically modified aluminum silicate nanofiber membrane.
[0005] Furthermore, the step (1) specifically comprises ultrasonically dispersing the aluminum silicate nanofibers in a mixture of ethanol and water, then adding an aminosilane coupling agent for stirring and reacting, and filtering, washing and drying after the reaction to obtain amino-treated aluminum silicate nanofibers, wherein the mass ratio of the aluminum silicate nanofibers to the aminosilane coupling agent is 1:(0.1-0.5).
[0006] Furthermore, the stirring reaction in step (1) is refluxed at 80-90° C. for 10-16 hours, and the aminosilane coupling agent is one of 3-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.
[0007] Furthermore, the step (2) specifically comprises ultrasonically dispersing the amino aluminum silicate nanofibers in acetonitrile, adding 1,3-dichloropropanol and an acid binding agent under nitrogen protection, stirring and reacting, then adding the polyamino compound, continuing to stir and react, filtering and washing after the reaction, and drying to obtain the multifunctional aluminum silicate nanofibers, wherein the mass ratio of the amino aluminum silicate nanofibers, 1,3-dichloropropanol, the acid binding agent and the polyamino compound is 1: (0.3-0.7): (1.5-2.5): (0.5-2), and the acid binding agent is one of triethylamine and pyridine.
[0008] Furthermore, the stirring reaction in step (2) is performed under reflux at 60-70° C. for 8-12 hours.
[0009] Furthermore, the polyamino compound is one of triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine.
[0010] Furthermore, the step (3) specifically comprises ultrasonically dispersing the multifunctional aluminum silicate nanofibers in anhydrous ethanol, adding 2-butenal, stirring to react, and filtering, washing, and drying after the reaction to obtain multifunctional aluminum silicate nanofibers rich in double bonds, wherein the dosage ratio of the multifunctional aluminum silicate nanofibers to 2-butenal is 1 g: (2 to 3) ml.
[0011] Furthermore, the stirring reaction in step (3) is carried out at room temperature for 3 to 5 hours.
[0012] Furthermore, the step (4) specifically comprises ultrasonically dispersing the double-bond-rich multifunctional aluminum silicate nanofibers in N , N -dimethylformamide solution, adding itaconic acid and initiator azobisisobutyronitrile under protective atmosphere to carry out cross-linking polymerization reaction, wherein the mass ratio of double-bond-rich multifunctional aluminum silicate nanofibers, itaconic acid and azobisisobutyronitrile is 1: (1-3): (0.02-0.04).
[0013] Furthermore, the cross-linking polymerization reaction in step (4) is carried out at 60-100° C. for 12-20 hours.
[0014] The present invention first uses 1,3-dichloropropanol as a "bridge" to graft polyamino compounds onto the surface of amino-modified aluminum silicate nanofibers, thereby introducing a large number of hydroxyl groups, amino groups and imine groups on the surface. Further, by means of an ammonia-aldehyde condensation reaction, 2-butenal is grafted onto the surface of the multifunctionalized fiber, thereby introducing double bonds on the surface. Finally, starting from the interface structure design, the prepared multifunctionalized aluminum silicate nanofibers rich in double bonds are used as a crosslinking agent, and itaconic acid containing double bonds and multiple carboxyl groups is used as a monomer to carry out a crosslinking copolymerization reaction, which not only realizes the crosslinking modification of the aluminum silicate nanofibers, but also further introduces a large number of carboxyl groups with adsorption activity. Thus, with the help of a simple vacuum filtration technology, an aluminum silicate nanofiber composite membrane with excellent structural stability and adsorption performance is prepared.
[0015] The advantages of the present invention compared with the prior art are: The present invention firstly greatly enriches the types and quantities of functional groups on the surface of aluminum silicate nanofibers through a multi-step modification method, further introduces double bonds on the surface of multi-functional group modified aluminum silicate nanofibers, and introduces polymerization monomers to perform cross-linking polymerization modification between fibers, which not only forms a good interface bond, but also introduces more heavy metal ion binding sites. A multi-functional group synergistic modified aluminum silicate nanofiber membrane with excellent structural stability and adsorption performance is prepared through a simple filtration technology, achieving its efficient adsorption of heavy metals, while solving the problem that nano powder materials are not easy to recycle, and effectively promoting the application of magnesium silicate nanofibers in the field of adsorption. DETAILED DESCRIPTION
[0016] The present invention will be further described below in conjunction with the embodiments, but are not intended to limit the present invention.
[0017] Example 1
[0018] A method for preparing a multi-functional group synergistically modified aluminum silicate nanofiber membrane comprises the following steps: (1) 1g of aluminum silicate nanofibers were ultrasonically dispersed in anhydrous ethanol, 0.1g of 3-aminopropyltrimethoxysilane was added, and the mixture was stirred under reflux at 80°C for 16h. After the reaction, the mixture was filtered, washed alternately with ethanol and deionized water, and dried to obtain amino-modified aluminum silicate nanofibers. The aluminum silicate nanofibers were sourced from Shanghai MacLean Biochemical Technology Co., Ltd., CAS: 1327-36-2. The aluminum silicate nanofibers used below were sourced from the same source.
[0019] (2) 1 g of amino-modified aluminum silicate nanofibers was ultrasonically dispersed in acetonitrile. Under nitrogen protection, 0.3 g of 1,3-dichloropropanol and 1.5 g of triethylamine were added. The mixture was stirred and reacted at 60 °C for 12 h. Then, 0.5 g of triethylenetetramine was added and the mixture was stirred and reacted at 60 °C for 12 h. After the reaction, the mixture was filtered, washed alternately with ethanol and deionized water, and dried to obtain multifunctional aluminum silicate nanofibers.
[0020] (3) Ultrasonic dispersion of 1 g of multifunctional aluminum silicate nanofibers in anhydrous ethanol, addition of 2 ml of 2-butenal, stirring at room temperature for 3 h, and after the reaction, filtration, ethanol and deionized water washing alternately, and drying were performed to obtain multifunctional aluminum silicate nanofibers rich in double bonds.
[0021] (4) 1 g of multifunctional aluminum silicate nanofibers rich in double bonds was ultrasonically dispersed in N , N -dimethylformamide solution, under N2 protection, add 1g of itaconic acid and 0.02g of azobisisobutyronitrile, stir and react at 60℃ for 20h, cool to room temperature, add solvent to the reaction system to reach 2000mL, take 38.9mL of reaction solution for suction filtration, wash repeatedly with deionized water, and peel off the sample membrane from the filter membrane after drying to obtain a sample with a diameter of 10cm and a gram weight of 5g / m 2 Multi-functional groups synergistically modified sodium silicate nanofiber membrane.
[0022] The adsorption performance test experiment of the multi-functional group synergistic modified aluminum silicate nanofiber membrane prepared in Example 1 is as follows: Prepare 100 mL of an aqueous solution with a lead ion concentration of 100 mg / L (lead nitrate as a reagent) in a flask, adjust the solution pH to 7 with 0.1 M NaOH, add the prepared multi-functional group synergistic modified aluminum silicate nanofiber membrane, and then adsorb for 3 hours at 200 rpm in a constant temperature oscillator at 30°C. After adsorption, take the upper clear liquid, determine the lead ion concentration in the clear liquid by ICP-OES, and calculate the adsorption amount of lead ions by the adsorbent material by the following formula ( Q , mg / g), and the results are listed in Table 1.
[0023] Q =( C 0 - C t ) V / M Q is the adsorption amount (mg / g); C 0 is the initial concentration of heavy metal ions (mg / L); C t is the concentration of heavy metal ions after adsorption (mg / L);V is the volume of the solution (L); M is the mass of the adsorbent (mg).
[0024] Example 2
[0025] A method for preparing a multi-functional group synergistically modified aluminum silicate nanofiber membrane comprises the following steps: (1) 1 g of aluminum silicate nanofibers was ultrasonically dispersed in anhydrous ethanol, and 0.3 g of 3-aminopropyltrimethoxysilane was added. The mixture was refluxed and stirred at 85 °C for 13 h. After the reaction, the mixture was filtered, washed alternately with ethanol and deionized water, and dried to obtain amino aluminum silicate nanofibers.
[0026] (2) 1 g of amino-modified aluminum silicate nanofibers was ultrasonically dispersed in acetonitrile. Under nitrogen protection, 0.5 g of 1,3-dichloropropanol and 2 g of triethylamine were added. The mixture was stirred and reacted at 65 °C for 10 h. Then, 1.25 g of triethylenetetramine was added and the mixture was stirred and reacted at 65 °C for another 10 h. After the reaction, the mixture was filtered, washed alternately with ethanol and deionized water, and dried to obtain multifunctional aluminum silicate nanofibers.
[0027] (3) 1 g of multifunctional aluminum silicate nanofibers was ultrasonically dispersed in anhydrous ethanol, 2.5 ml of 2-butenal was added, and the mixture was stirred at room temperature for 4 h. After the reaction, the mixture was filtered, washed alternately with ethanol and deionized water, and dried to obtain multifunctional aluminum silicate nanofibers rich in double bonds.
[0028] (4) 1 g of multifunctional aluminum silicate nanofibers rich in double bonds was ultrasonically dispersed in N , N -dimethylformamide solution, under N2 protection, add 2g of itaconic acid and 0.03g of azobisisobutyronitrile, stir and react at 80℃ for 16h, cool to room temperature, add solvent to the reaction system to reach 2000mL, take 51.8mL of reaction solution for suction filtration, wash repeatedly with deionized water, and peel off the sample membrane from the filter membrane after drying to obtain a sample with a diameter of 10cm and a gram weight of 10g / m 2 Multi-functional groups synergistically modified sodium silicate nanofiber membrane.
[0029] Example 3
[0030] A method for preparing a multi-functional group synergistically modified aluminum silicate nanofiber membrane comprises the following steps: (1) 1 g of aluminum silicate nanofibers was ultrasonically dispersed in anhydrous ethanol, 0.5 g of 3-aminopropyltrimethoxysilane was added, and the mixture was refluxed and stirred at 90 °C for 10 h. After the reaction, the mixture was filtered, washed alternately with ethanol and deionized water, and dried to obtain amino aluminum silicate nanofibers.
[0031] (2) 1 g of amino-modified aluminum silicate nanofibers was ultrasonically dispersed in acetonitrile. Under nitrogen protection, 0.7 g of 1,3-dichloropropanol and 2.5 g of triethylamine were added. The mixture was stirred and reacted at 70 °C for 8 h. Then, 2 g of triethylenetetramine was added and the mixture was stirred and reacted at 70 °C for another 8 h. After the reaction, the mixture was filtered, washed alternately with ethanol and deionized water, and dried to obtain multifunctional aluminum silicate nanofibers.
[0032] (3) Ultrasonic dispersion of 1 g of multifunctional aluminum silicate nanofibers in anhydrous ethanol, addition of 3 ml of 2-butenal, stirring at room temperature for 5 h, and after filtration, washing with ethanol and deionized water alternately, and drying, obtain multifunctional aluminum silicate nanofibers rich in double bonds.
[0033] (4) 1 g of multifunctional aluminum silicate nanofibers rich in double bonds was ultrasonically dispersed in N , N -dimethylformamide solution, under N2 protection, add 3g of itaconic acid and 0.04g of azobisisobutyronitrile, stir and react at 100℃ for 20h, cool to room temperature, add solvent to the reaction system to reach 2000mL, take 58.3mL of reaction solution for suction filtration, wash repeatedly with deionized water, and peel off the sample membrane from the filter membrane after drying to obtain a sample with a diameter of 10cm and a gram weight of 15g / m 2 Multi-functional groups synergistically modified sodium silicate nanofiber membrane.
[0034] Example 4
[0035] A method for preparing a multi-functional group synergistically modified aluminum silicate nanofiber membrane, wherein steps (1), (2), and (3) are the same as those in Example 1, and step (4) is to ultrasonically disperse 1 g of multi-functional aluminum silicate nanofibers rich in double bonds in a N , N -dimethylformamide solution, under N2 protection, add 1g of itaconic acid and 0.02g of azobisisobutyronitrile, stir and react at 60℃ for 20h, cool to room temperature, add solvent to the reaction system to reach 2000mL, take 77.8mL of reaction solution for suction filtration, wash repeatedly with deionized water, and peel off the sample membrane from the filter membrane after drying to obtain a sample with a diameter of 10cm and a gram weight of 10g / m 2 Multi-functional groups synergistically modified sodium silicate nanofiber membrane.
[0036] Example 5
[0037] A method for preparing a multi-functional group synergistically modified aluminum silicate nanofiber membrane, wherein steps (1), (2), and (3) are the same as those in Example 1, and step (4) is to ultrasonically disperse 1 g of multi-functional aluminum silicate nanofibers rich in double bonds in a N , N-dimethylformamide solution, under N2 protection, add 1g of itaconic acid and 0.02g of azobisisobutyronitrile, stir and react at 60℃ for 20h, cool to room temperature, add solvent to the reaction system to reach 2000mL, take 116.7mL of reaction solution for suction filtration, wash repeatedly with deionized water, and peel off the sample membrane from the filter membrane after drying to obtain a sample with a diameter of 10cm and a gram weight of 15g / m 2 Multi-functional groups synergistically modified sodium silicate nanofiber membrane.
[0038] Comparative Example 1 1 g of original aluminum silicate nanofibers was ultrasonically dispersed in 2000 mL of N , N - dimethylformamide, ultrasonically dispersed evenly, 78.5 mL of the reaction solution was filtered, washed repeatedly with deionized water, and after drying, the sample membrane was peeled off from the filter membrane to obtain a sample with a diameter of 10 cm and a gram weight of 5 g / m 2 The adsorption performance of the pure sodium silicate nanofiber membrane was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.
[0039] Comparative Example 2 The aminated magnesium silicate nanofibers were prepared according to step (1) in Example 1, and then 1 g of aminated aluminum silicate nanofibers were ultrasonically dispersed in 2000 mL of N , N - dimethylformamide, ultrasonically dispersed evenly, 78.5 mL of the reaction solution was filtered, washed repeatedly with deionized water, and after drying, the sample membrane was peeled off from the filter membrane to obtain a sample with a diameter of 10 cm and a gram weight of 5 g / m 2 The adsorption performance of the amino-modified sodium silicate nanofiber membrane was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.
[0040] Comparative Example 3 According to steps (1) and (2) in Example 1, multifunctional aluminum silicate nanofibers were prepared, and then 1 g of multifunctional aluminum silicate nanofibers were ultrasonically dispersed in 2000 mL of N , N - dimethylformamide, ultrasonically dispersed evenly, 78.5 mL of the reaction solution was filtered, washed repeatedly with deionized water, and after drying, the sample membrane was peeled off from the filter membrane to obtain a sample with a diameter of 10 cm and a gram weight of 5 g / m 2 The adsorption performance of the multifunctional sodium silicate nanofiber membrane was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.
[0041] Comparative Example 4 According to steps (1), (2), and (3) in Example 1, multifunctional aluminum silicate nanofibers rich in double bonds were prepared, and then 1 g of multifunctional aluminum silicate nanofibers rich in double bonds were ultrasonically dispersed in 2000 mL of N , N - dimethylformamide, ultrasonically dispersed evenly, 78.5 ml of the reaction solution was filtered, washed repeatedly with deionized water, and after drying, the sample membrane was peeled off from the filter membrane to obtain a sample with a diameter of 10 cm and a gram weight of 5 g / m 2 The adsorption performance of the double-bond-rich multifunctional sodium silicate nanofiber membrane was measured according to the adsorption performance experiment of the product in Example 1, and the results are listed in Table 1.
[0042] Table 1 Adsorption amount of lead ions by aluminum silicate nanofiber membranes prepared in Examples 1-5 and Comparative Examples 1-3
[0043] It can be seen from the above results that the multi-functional group synergistic modified aluminum silicate nanofiber membrane prepared by the present invention exhibits excellent adsorption capacity for lead ions by virtue of its rich functional groups and strong covalent bond cross-linking structure between nanofibers. In particular, the more the number and types of functional groups on the surface of aluminum silicate nanofibers, the stronger the adsorption capacity of lead ions by the membrane, which is verified from the experimental data of Examples 1 to 5 and Comparative Examples 1 to 4.
[0044] By comparing the results of Example 1 with Comparative Example 4, it can be clearly seen that the cross-linked structure between aluminum silicate nanofibers plays an important role in improving the adsorption performance of the fiber membrane. Through cross-linking polymerization modification, the aluminum silicate nanofibers form a strong interface bond under the dual action of hydrogen bonds and covalent bonds, which effectively improves the permeation flux of the membrane. In addition, the cross-linking polymerization reaction process also introduces a large number of carboxyl functional groups, providing more abundant binding sites for heavy metal ions.
[0045] In addition, it is worth noting that although increasing the mass of the membrane can theoretically provide more adsorption sites, when the diameter remains unchanged, increasing the mass means increasing the thickness of the membrane. The increase in membrane thickness will hinder the entry of metal ions into the membrane, resulting in a decrease in mass transfer efficiency, which in turn affects the adsorption of metal ions. Therefore, when the thickness of the membrane exceeds a certain threshold, the growth of its actual adsorption amount will no longer meet expectations, and may even show a downward trend, as shown in the results of Examples 1, 4, and 5.
Claims
1. A method for preparing a multi-functional group synergistically modified aluminum silicate nanofiber membrane, characterized in that: The following steps are involved: (1) Aluminum silicate nanofibers are modified by using an aminosilane coupling agent to obtain amino-modified aluminum silicate nanofibers; (2) grafting the polyamino compound onto the surface of the amino-modified aluminum silicate nanofibers by a substitution reaction between amino groups and chlorine and utilizing the cross-linking effect of 1,3-dichloropropanol to obtain multifunctional aluminum silicate nanofibers; (3) modifying the surface of the multifunctional aluminum silicate nanofibers with 2-butenal by an ammonia-aldehyde condensation reaction, thereby obtaining multifunctional aluminum silicate nanofibers rich in double bonds; (4) using itaconic acid as a monomer and the double-bond-rich multifunctional aluminum silicate nanofibers as a crosslinking agent, performing crosslinking polymerization, and then performing suction filtration to form a membrane, and obtaining a film having a gram weight of no more than 15 g / m 2 Multi-functional groups synergistically modified aluminum silicate nanofiber membrane.
2. The method for preparing the multi-functional group synergistically modified aluminum silicate nanofiber membrane according to claim 1, characterized in that: The step (1) specifically comprises ultrasonically dispersing the aluminum silicate nanofibers in a mixture of ethanol and water, then adding an aminosilane coupling agent for stirring and reacting, and after the reaction, filtering, washing and drying to obtain amino-treated aluminum silicate nanofibers, wherein the mass ratio of the aluminum silicate nanofibers to the aminosilane coupling agent is 1:(0.1-0.5).
3. The method for preparing the multi-functional group synergistically modified aluminum silicate nanofiber membrane according to claim 2, characterized in that: The stirring reaction in step (1) is refluxed at 80-90° C. for 10-16 hours, and the aminosilane coupling agent is one of 3-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.
4. The method for preparing the multi-functional group synergistically modified aluminum silicate nanofiber membrane according to claim 1, characterized in that: The step (2) specifically comprises ultrasonically dispersing the amino aluminum silicate nanofibers in acetonitrile, adding 1,3-dichloropropanol and an acid binding agent under nitrogen protection, stirring and reacting, then adding the polyamino compound, continuing to stir and react, filtering and washing after the reaction, and drying to obtain the multifunctional aluminum silicate nanofibers, wherein the mass ratio of the amino aluminum silicate nanofibers, 1,3-dichloropropanol, the acid binding agent and the polyamino compound is 1: (0.3-0.7): (1.5-2.5): (0.5-2), and the acid binding agent is one of triethylamine and pyridine.
5. The method for preparing the multi-functional group synergistically modified aluminum silicate nanofiber membrane according to claim 4, characterized in that: The stirring reaction in step (2) is carried out under reflux at 60-70° C. for 8-12 hours.
6. The method for preparing the multi-functional group synergistically modified aluminum silicate nanofiber membrane according to claim 4, characterized in that: The polyamino compound is one of triethylenetetramine, tetraethylenepentamine and pentaethylenehexamine.
7. The method for preparing the multi-functional group synergistically modified aluminum silicate nanofiber membrane according to claim 1, characterized in that: The step (3) specifically comprises ultrasonically dispersing the multifunctional aluminum silicate nanofibers in anhydrous ethanol, adding 2-butenal, stirring to react, and filtering, washing, and drying after the reaction to obtain multifunctional aluminum silicate nanofibers rich in double bonds, wherein the dosage ratio of the multifunctional aluminum silicate nanofibers to 2-butenal is 1 g: (2 to 3) ml.
8. The method for preparing the multi-functional group synergistically modified aluminum silicate nanofiber membrane according to claim 7, characterized in that: The stirring reaction in step (3) is carried out at room temperature for 3 to 5 hours.
9. The method for preparing the multi-functional group synergistically modified aluminum silicate nanofiber membrane according to claim 1, characterized in that: The step (4) specifically comprises ultrasonically dispersing the double-bond-rich multifunctional aluminum silicate nanofibers in N , N -dimethylformamide solution, adding itaconic acid and initiator azobisisobutyronitrile under protective atmosphere to carry out cross-linking polymerization reaction, wherein the mass ratio of double-bond-rich multifunctional aluminum silicate nanofibers, itaconic acid and azobisisobutyronitrile is 1: (1-3): (0.02-0.04).
10. The method for preparing the multi-functional group synergistically modified aluminum silicate nanofiber membrane according to claim 9, characterized in that: The cross-linking polymerization reaction in step (4) is carried out at 60-100° C. for 12-20 hours.
Citation Information
Patent Citations
Process for the production of 2-methyl-2-alkenals from dihydropyranes
EP0168761A1
Product containing deodorant
JP2005065750A
Method for Producing Dialkylphosphinic Acids and Esters and Salts Thereof by Means of Allyl Alcohols-Acroleins and use Thereof
US20110201732A1
Process for producing particles of amine reaction product
US6451751B1
Cited By
Preparation method of polyfunctional group synergistic modified halloysite nanotube-based composite membrane
CN120169327A
Strong cationic nanofiber membrane and preparation method thereof
CN121016702A